Identification keys on rattans (Calamus spp.) from Central Sulawesi based on anatomical structure of stems - ANDI TANRA TELLU (Society for Indonesian Biodiversity, 2005)
This study was conducted to obtain information the anatomical characteristics of 20 rattan species from Central Sulawesi and to use it for anatomical identification of rattan species. The rattan comprised 16 Calamus species, three Daemonorops species and one Korthalsia species. For anatomical observation 10-15 mm pieces of the mature stem from shares of tip do not have frond were processed with polyethilene glycol 2000, cut at 18-32 Î¼m and stained with a combination of acridin-cryzoidin red and astrablue. Cleared preparation were used to observe stegmata, and macerated material was used to measure the length of fibers and vessel elements. Anilin sulfate was used to confirm the existence of lignin. Anatomical characteristics used in identification were shape and will thickening of epidermal cells and the position stomata at epidermal; the arrangement of sub epidermal parenchyma; composition of vascular bundles and their distribution; the shape and arrangement of central ground parenchyma and the occurrence of fiber bundles. The research result indicated that the anatomical character can be compiled to a key identify the rattan at genus and species level.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: rattan, identification, anatomical characteristics.